Punti Kayu Berdaya: Strategi Pengabdian Masyarakat dalam Menggerakkan Ekonomi Lokal Melalui Ekowisata - M Bambang Purwanto; Dwi Hanadya; Nyanyu Ully Auliana; Edi Harapan; Agung Indriansyah (Jurnal Pelayanan Masyarakat, 2025)
The Punti Kayu Tourism Forest has great potential in maintaining environmental balance and improving the local economy. However, this potential has not been utilized optimally due to lack of public awareness and limited skills. This community service activity aims to increase public awareness about the economic and educational potential of the Punti Kayu Tourism Forest, provide training and assistance in utilizing the potential of the tourism forest, and encourage the development of creative economy products based on the tourism forest. The method used is counselling and socialization, which is carried out by the Prasetiya Mandiri Polytechnic Lecturer Team, PSDKU Palembang, on April 10, 2025. The results of the activity showed an increase in the number of visitors to the tourist forest, an increase in the income of local communities, and an increase in public awareness about the importance of conservation. The interpretation of the results shows that this community service activity has had a significant positive impact on the community and the environment. The conclusion of this activity is that community empowerment through education and training is the key to success in utilizing the potential of urban forests in a sustainable manner.